Centromeric RNA and Its Function at and Beyond Centromeric Chromatin. Issue 15 (10th July 2020) - Corless, Samuel; Höcker, Saskia; Erhardt, Sylvia
Abstract: The most fundamental region of the chromosome for maintaining accurate genome segregation and stability is the centromeric chromatin [1, 2 ]. In this review, we will focus on centromere-derived RNAs (cenRNAs), a crucial component of centromere structure first identified over 40 years ago [3 ] but only recently investigated in detail. Indeed, centromeric transcription is necessary for the proper formation of CENP-A-containing centromeric chromatin (cen-chromatin) [4–7 ] and for the formation of pericentromeric heterochromatin [8, 9 ], and the transcripts play a role in the structure and function of the centromere–kinetochore interface [3, 7, 10 ]. Furthermore, cenRNA overexpression has been observed in some cancer patients [11–13 ] and has been shown to drive the formation of breast cancer in a mouse model system [14 ]. Together, these observations call for a more detailed appraisal of the composition, regulation and function of cenRNAs. In this review, we will first discuss the difficulties underlying the study of cenRNAs, then we identify different domains within the centromeric chromatin before we discuss the role of cenRNAs in the context of these domains. Graphical abstract: Unlabelled Image Highlights: RNAs associate with centromeric chromatin. Centromeres are transcribed. Centromeric chromatin can be divided into different subdomains. RNAs are essential for the function of centromeric subdomains. RNA needs to be considered an essential part of centromere structure and function.